Expanding “Communities and Collections” in the K-State Research Exchange (K-REx) to benefit the K-State Community and Beyond - Finch, Emily; Coleman, Tara (My University, 2021)
Kansas State University has used its institutional repository, the K-State Research Exchange (K-REx), to store and share its first year experience program, K-State First, and notably its common reading program, K-State First Book. We have done so with the aim that the accessibility and preservation of these documents ensures program stability, promotes engagement with first year programming, and provides the ability to foster growth,educational opportunities, and community building outside of K-State. Moving away from research concentrated repositories and taking a more holistic approach to scholarship, especially when realizing the pedagogical significance of collaborative campus programming, institutions can showcase, discover, preserve, and grow programs that shape campus communities and engagement. This session will provide an overview of K-REx and spotlight the digital archive of the university’s first year experience program and common reading program, K-State First Book. We will discuss the benefits and challenges to expanding the purview of your repositories. We talkthrough the types of materials we decide to host in our repository and why we share what we do. We will also provide recommendations on new ways to evaluate what belongs in institutional repositories and how this diversity can benefit your program, your institution, the community, and others.
Keywords: K-State research exchange; Institutional repository; K-State first book; Scholarly communication; Collections; Digital scholarship